(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: BPH is one of the most common cause of LUTS which significantly impairs the quality of life. TURP is minimally invasive surgical procedure for Benign Prostatic hyperplasia which has impact on quality of life. Impact on quality of life can be measured by QoL score and effect of TURP can be evaluated. Objective: The purpose of the present study was to evaluate the impact of transurethral resection of prostate (TURP) on Quality of Life (QoL) score. Methodology: This prospective study was carried out in the Department of Urology, Shaheed Suhrawardy Medical College and Hospital, Dhaka, from July 2015 to June 2016. Total fifty patients between 50 to 72 years attending for the treatment of benign prostatic hypertrophy (BPH) with lower urinary tract symptoms (LUTS) were included for the study according to inclusion & exclusion criteria. All of them were evaluated with baseline international prostate symptoms score (IPSS), QoL score, peak urinary flow rate (Qmax), voided volume, voiding time and PVR and were recorded in a predesigned data sheet. Selected patients underwent Transurethral Resection of Prostate. They were followed after 1 month and 3 months with same parameter and compared with the baseline values. Results: The baseline international prostate symptoms score (IPSS) in this study was 25.18±1.45. At one month and three months follow up visits after TURP, the IPSS was decreased to 15.0±1.07 and 8.14±0.76 respectively. There was significant improvement of peak urinary flow rate (Qmax) in the postoperative period, at the 1st follow up visit after one month of TURP (15.78±1.42, p<0.001) and at the 2nd follow visit after three months of TURP (18.78, p <0.001). The mean QoL score was 5.30±0.46 before TURP. After one month of TURP it was 3.20±0.45 and after 3 months of TURP it was 1.86±0.57. Conclusion: There is a significant improvement of quality of after TURP. Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 143-147